Comparison of arbitrarily primed polymerase chain reaction, ribotyping, and monoclonal antibody analysis for subtyping Legionella pneumophila serogroup 1. - Gomez-Lus, P (1993)
Arbitrarily primed polymerase chain reaction (AP-PCR) was used to characterize Legionella pneumophila serogroup 1. Cells from a single colony could be subtyped by AP-PCR within a few hours. The discrimination between strains of L. pneumophila serogroup 1 by AP-PCR was equivalent to that by monoclonal antibody analysis and ribotyping. Four strains representing the monoclonal antibody pattern most frequently associated with outbreaks all yielded unique amplicon patterns by AP-PCR.